2017
DOI: 10.7448/ias.20.01/21422
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sex work involvement among transgender women in Jamaica: a cross‐sectional study

Abstract: Introduction: Transgender women are disproportionately impacted by HIV. Transgender women involved in sex work may experience exacerbated violence, social exclusion, and HIV vulnerabilities, in comparison with non-sex work-involved transgender women. Scant research has investigated sex work among transgender women in the Caribbean, including Jamaica, where transgender women report pervasive violence. The study objective was to examine factors associated with sex work involvement among transgender women in Jama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 49 publications
(99 reference statements)
0
37
0
1
Order By: Relevance
“…Another study showed 36.9% of female sex workers suffer from partner physical abuse and are associated with higher rates of mental health problems [ 59 ]. Higher rates of sex work were found in African female sex workers facing intimate partner violence [ 61 , 62 ]. In fact, a study conducted in India on female sex workers showed that many young married girls are beaten and abused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed 36.9% of female sex workers suffer from partner physical abuse and are associated with higher rates of mental health problems [ 59 ]. Higher rates of sex work were found in African female sex workers facing intimate partner violence [ 61 , 62 ]. In fact, a study conducted in India on female sex workers showed that many young married girls are beaten and abused.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study conducted in India on female sex workers showed that many young married girls are beaten and abused. This sexual and physical exploitation could be a motive for being a sex worker [ 61 , 62 ]. The emotional stress and the resulting mental health illnesses faced by women can consequently influence their choice of becoming a sex worker.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that discrimination had a significant impact on HIV care continuum indicators for transwomen living with HIV [6,[24][25][26][29][30][31][32][33]. Prior experiences of anti-trans discrimination were associated with delays in HIV testing…”
Section: Discussionmentioning
confidence: 99%
“…Yes (no is reference) 6.28 (1.37 to 28.70), p = 0. among transwomen in Brazil and Jamaica [32,33]. The effects of anti-trans discrimination may be particularly pronounced for transwomen of colour, who also face racism and bear the largest burden of HIV in the transwomen population [23,24,31].…”
Section: Gender and Race Discriminationmentioning
confidence: 99%
“…Therefore, this study uses the “syndemics” framework to investigate the effects of alcohol misuse, poly-drug use, sexual violence experience, and history of childhood sexual abuse on unprotected sex with three different categories of partners, namely, regular, occasional, and transactional. In transgender women, transactional sex is particularly important in HIV risk acquisition and is related to greater exposure to psychosocial problems 17 , 18 and their accumulation 19 . In MSM, the co-occurrence of psychosocial problems on transactional sex has been less explored despite the high risk of HIV among individuals engaged in transactional sex 20 , 21 and the associations found between experiences of childhood abuse and sexual violence with higher odds of reporting transactional sex 22 .…”
mentioning
confidence: 99%